Analisis Faktor Prediksi Peningkatan Kontrol Glikemik Pada Pasien Diabetes Melitus Tipe 2 Di RSUD Abdul Moeloek Provinsi Lampung Periode Januari-Desember 2022 - Yovani Tria Ananda; Intanri Kurniati; Novita Carolia; Putu Ristyaning Ayu Sangging (CV. Jasa Sukses Abadi, 2026)
The 2018 Basic Health Research report indicated that prevalence of Diabetes Mellitus (DM) in Indonesia increased to 8,3%. This rise was accompanied by an increase in obesity prevalence, a major risk factor for DM, from 14,8% in 20113 to 21,8% in 2018. These findings suggest that the number of individuals with DM in Indonesia is substantial and continues to grow annually. Data from Bandar Lampung City in 2021 showed that out of 6,467,624 individuals aged ≥15 years, approximately 198,046 (3%) were diagnosed with DM. This study aimed to analyze the association between predictive factors and glycemic control among patients with type 2 diabetes mellitus at Abdul Moeloek Hospital, Lampung Province, during January-December 2022. This research employed an observational study with a cross-sectional design. Secondary data were obtained from medical records of both inpatient and outpatient type 2 diabetes mellitus patients. Data analysis was performed using the Chi-Square test, with the Mann-Whitney test as an alternative. The result demonstrated significant associations between age at diagnosis (p=0,006), duration of Diabetes (p=0,012), body mass index (p=0,016), and comorbidities (p=0,020) with glycemic control. In conclusion, age at diagnosis, duration of disease, body mass index, and comorbid conditions were significantly associated with glycemic control among patients with type 2 diabetes mellitus receiving oral antidiabetic drugs and insulin therapy at Abdul Moeloek Hospital, Lampung Province, during January-December 2022.